Designing Interactive Seminars to Teach Clinical Management of Chest Pain: Lessons from the Trenches - Kendalle Cobb; S. Beth Bierer (Association of American Medical Colleges, 2012)
Abstract This module contains a chest pain case specifically designed for instructional purposes to help third-year medical students build upon prior knowledge, develop data-collection skills, synthesize complex information, and formulate and test hypotheses. The case also provides opportunities for learners to discuss women's chest pain, a frequently overlooked symptom, and explore biases (i.e., alcohol use, smoking, poor diet, etc.) that may impact patient care. Ideally, instructors who use this teaching case should be clinicians with content expertise and can recognize third-year medical students' level of knowledge. These clinicians should also possess the ability to lead large-group discussions. Previous experience with case-based instruction is not essential for those who want to adopt this case for clerkship teaching. Curriculum planners should allot approximately 1-2 hours for students to discuss this case depending upon group size (usually 20-30 learners). We hope that this teaching case serves as a template for institutions that wish to implement a case-based curriculum for clerkship teaching. Consequently, we have also included a file that describes the design, implementation, and evaluation of how we used clinical cases to deliver a 16-week curriculum to third-year medical students enrolled in an integrated clerkship (surgery, internal medicine, and family medicine). Our experience demonstrates that it is feasible for busy physicians to teach clerkship students in large-group settings using instructional cases of patients. The vast majority (over 90%) of our students indicated on the clerkship evaluation that case-based instruction enhanced their diagnostic acumen, helped them integrate knowledge across disciplines, encouraged discussion among students and faculty, and featured challenging clinical cases. Additionally, over 70% of our faculty have continued to teach case-based seminars 3 years after we first implemented our case-based clerkship curriculum. These findings are significant given current challenges to retain talented clinical instructors and create active learning environments for students.